Building a Prototype of an Eco-friendly House in the Peri-Urban Area - Allis Nurdini; Endra Susila; Taufik Taufikurahman; Nur Fitra Hadianto; Maryam Al Lubbu; Asih Suryati (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2021)
The concept of sustainable housing has considered the urgency to support the sustainable environment in an integrative way. This concept is related to several main principles include environmental, social, and economic sustainability. In practice, these principles translated into the fundamental of housing choice, both process and product choices. In many peri-urban areas, current house construction tends to imitate city houses with massive concrete structures equipped with air conditioning that caused high energy consumption. The Center for Rural Empowerment team of ITB built a prototype of an eco-friendly house in Haurgombong village, Sumedang, West Java. The house has two floors building on a 7x5 m2 land site. The first floor was renovated from the existing toilet rooms and develop into a two-floor house. The second floor was built using the local wood material. The wood material has been obtaining from the trees of seven years old beechwood (Gmelina Arborea) planted in the garden. The envelope material for this house was constructed from local and common material in rural or peri-urban context, the lightweight fiberglass for the roof of common room, and the transparent fiber materials for the roof of second-floor terrace to make the plantation at this area can easily receive the sunlight. This house is also can be regarded as a prototype of an earthquake-resistant house. The lighting factor, temperature, and airflow settings are made naturally. Besides, this house has also equipped with a rainwater storage system and greywater treatment using a small, constructed wetland that allows the treated water used for watering gardens and fishponds. The budget spent to build this house was as low as possible so that the surrounding community can imitate the building for their house and disseminate eco-friendly housing.